Psychodiden aus Mittelasien und angrenzenden Gebieten (Insecta, Diptera, Psychodidae). - Wagner, Rüdiger (Contributions to Entomology = Beiträge zur Entomologie, 2003)
Panimerus elongatus Wagner [Iran], Peripsychoda iranica Ježek [Iran], Satchelliella gracilis kandavanica Ježek [Iran], Thornburghiella globulipyga Ježek [China], T. kaszabi (Vaillant) [Russia, China], Satchelliella borealis (Berdén) [Russia], Satchelliella canescens (Meigen) [China, Kirgisia], Satchelliella stammeri (Jung) [China], Bazarella centuretinacula Wagner [China], Pericoma kabulica Wagner [Kirgisia], Pericoma tienshanensis Ježek [China], Paramormia ustulata (Walker) [China], Psychoda parthenogenetica Tonnoir [China], and Tinearia lativentris (Berdén) [China] are recorded. Thornburghiella xinjiangensis sp. n. [China], Bazarella pilosa sp. n. [China], Bazarella septentrionalis sp. n. [Russia], Bazarella baikalensis sp. n. [Russia], Pericoma sinica sp. n. [China], Psychoda meyi sp. n. [China], and Psychoda tiencensis sp. n. [China] are described and figured, and their phylogenetic relations are discussed. The areas of distribution of Central Asian Psychodidae are vast compared to those of European species.KeywordsDiptera, Psychodidae, new species, Central Asia, distribution.Nomenclatural Actsbaikalensis Wagner, 2003 (Bazarella), spec. n.pilosa Wagner, 2003 (Bazarella), spec. n.septentrionales Wagner, 2003 (Bazarella), spec. n.sinica Wagner, 2003 (Pericoma), spec. n.meyi Wagner, 2003 (Psychoda), spec. n.tiencensis Wagner, 2003 (Psychoda), spec. n.xinjiangensis Wagner, 2003 (Thornburghiella), spec. n.